Growing skull fracture of the orbital roof in a pediatric patient: challenges and outcomes of surgical treatment - Martínez, Dámaris; Salerno, Mariela C.; Colombo, Gonzalo; Tello Brogiolo, Nicolás; Tornesello Galván, Bárbara (Revista Argentina de Neurocirugía, 2025)
Background: skull fractures are common injuries associated with pediatric traumatic brain injury (TBI). Although most are linear and have a favorable outcome, they can occasionally be complicated by a growth fracture, primarily in children under 3 years of age. This is characterized by a progressive bone defect associated with a dural tear and herniation of brain tissue, which impedes normal healing. Objectives: to analyze the surgical management of an expanding orbital roof fracture in a pediatric patient. Case description: a 2-year-old male patient with mild TBI following a fall from height. He initially presented with a linear fracture of the right orbital roof with no associated injuries or neurological deficits. At 3 months of age, he developed eyelid ptosis, strabismus, and weakness in the right ocular muscles. Imaging studies showed widening of the fracture line and brain herniation into the orbital cavity. Surgical treatment was performed. Surgery: a frontal craniotomy, dissection and resection of the fibrous tract, duroplasty with pericranial cement, and cranioplasty with bone cement were performed. Absorbable plates and screws were used for bone fixation. The postoperative course was favorable, with significant clinical improvement. Conclusion: we present an atypical case of a growing orbital roof fracture in a pediatric patient and its surgical resolution. The importance of timely diagnosis and proper treatment, including duroplasty and cranioplasty, is emphasized to avoid cosmetic, neurological, and functional sequelae.